2001
DOI: 10.1073/pnas.161285698
|View full text |Cite
|
Sign up to set email alerts
|

Myosin I mutants with only 1% of wild-type actin-activated MgATPase activity retain essentialin vivofunction(s)

Abstract: The single class I myosin (MYOA) of Aspergillus nidulans is essential for hyphal growth. It is generally assumed that the functions of all myosins depend on their actin-activated MgATPase activity. Here we show that MYOA mutants with no more than 1% of the actin-activated MgATPase activity of wild-type MYOA in vitro and no detectable in vitro motility activity can support fungal cell growth, albeit with a delay in germination time and a reduction in hyphal elongation. From these and other data, we conclude tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 45 publications
1
27
2
Order By: Relevance
“…7A). Three observations indicated that this Arp3-GFP fusion protein is associated with cortical actin patches, as in S. cerevisiae (40). First, the Arp3-GFP signal was localized in patches at the hyphal tips of the wildtype strain (Fig.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…7A). Three observations indicated that this Arp3-GFP fusion protein is associated with cortical actin patches, as in S. cerevisiae (40). First, the Arp3-GFP signal was localized in patches at the hyphal tips of the wildtype strain (Fig.…”
mentioning
confidence: 73%
“…In Aspergillus, replacement of the TEDS-rule site with alanine dramatically affected the Mg 2ϩ -ATPase activity of myosin I, whereas replacement with the phosphorylation mimic glutamic acid reduced but did not abolish this activity, suggesting that ATPase activity in MyoA is subject to modulation by phosphorylation of the TEDS-rule site. However, the significance of this phosphorylation is not clear because both of the myoA substitution mutants are equally functional in restoring the viability of the null mutant (40).…”
mentioning
confidence: 99%
“…It is possible that some contractile activity below the limit of our assays is present in ELC-myosin, and this is sufficient to allow myosin II to integrate the cortex. It has been determined that Aspergillus nidulans myosin I mutants with less than 1% of wild-type actin-activated MgATPase activity retain essential in vivo functions (Liu et al, 2001). However, we have shown that mlcE -cells cannot undergo contraction of detergent extracted cortices, which would be a direct test of contractile activity of myosin in situ (Xu et al, 2001).…”
mentioning
confidence: 99%
“…Since some of the fungal myosins I do not require phosphorylation to fulfill their cellular tasks (22,23), we decided to first investigate if the S. cerevisiae Myo5p TEDS site was phosphorylated in vivo. In order to address this matter, the wild type Myo5p or a mutant bearing a TEDS serine to alanine substitution (Myo5-S357Ap) was immunoprecipitated from 32 PO 4 3Ϫ -radiolabeled yeast cells.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, the yeast MYO3 TEDS site serine to alanine mutant (myo3-S357A) fails to complement the synthetic lethal phenotype of a double myo3⌬ myo5⌬ null strain (20,21). Interestingly, however, not all fungal myosin I functions require phosphorylation of this residue and/or full ATPase activity, since a TEDS site to alanine mutation in the Aspergillus nidulans MYOA only causes slight defects when compared with the null mutation (22,23).…”
mentioning
confidence: 94%